2022
DOI: 10.1158/2326-6066.cir-21-0778
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Derived Lactic Acid Modulates Activation and Metabolic Status of Draining Lymph Node Stroma

Abstract: Communication between tumors and the stroma of tumor-draining lymph nodes (TDLN) exists before metastasis arises, altering the structure and function of the TDLN niche. Transcriptional profiling of fibroblastic reticular cells (FRC), the dominant stromal population of lymph nodes, has revealed that FRCs in TDLNs are reprogrammed. However, the tumor-derived factors driving the changes in FRCs remain to be identified. Taking an unbiased approach, we have shown herein that lactic acid (LA), a metabolite released … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Lactic acid is known to be enriched in the fraction (<3 kDa) of tumor‐conditioned medium. [ 25 ] Hence, we fractionated the tumor‐conditioned medium by size (<3 kDa) and found that the M2‐like TAM polarization was reduced in KO macrophages under incubation with the fraction compared to WT macrophages (<3 kDa) (Figure 3D ; Figure S3D,E , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Lactic acid is known to be enriched in the fraction (<3 kDa) of tumor‐conditioned medium. [ 25 ] Hence, we fractionated the tumor‐conditioned medium by size (<3 kDa) and found that the M2‐like TAM polarization was reduced in KO macrophages under incubation with the fraction compared to WT macrophages (<3 kDa) (Figure 3D ; Figure S3D,E , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, sapanisertib, PHA-793887, and ciclopirox decreased extracellular lactate concentration in Ishikawa and HEC-1B cells. Other groups have shown that lactate accumulation, and, therefore, acidic microenvironment, is a major factor in cancer cell invasiveness and lymph node metastatic colonization 73 , 74 . These observations highlight the potential benefit of targeting cancer acidity and/or lactate accumulation in EC.…”
Section: Discussionmentioning
confidence: 99%
“…FRCs can also shape the premetastatic niche through various other mechanisms. Riedel et al 84 showed that before metastatic colonization, tumor-derived lactic acid could drain to LNs, contributing to IL-7 downregulation and altered FRC mitochondrial function. IL-1 production by melanoma cells can suppress FRC contractility through JAK1/STAT3 pathway inhibition, with the consequent relaxation of the 3D FRC network, better-enabling melanoma cells to invade this niche.…”
Section: Molecular Mechanisms Of Lymph Node Metastasismentioning
confidence: 99%